PRODUCTIVITY AND FRESH SEMEN CHARACTERISTICS OF SIMMENTAL BULL DIFFERENT AGES - Satrio, Faisal Amri; Karja, Ni Wayan Kurniani; Setiadi, Mohamad Agus; Kaiin, Ekayanti Mulyawati; Kurnia, Asep; Purwantara, Bambang (Jurnal Kedokteran Hewan, 2022)
This study aimed to determine the effect of age on bulls productivity and fresh semen characteristics of Simmental bull in Indonesia. A total of 1071 data of semen collection and production from four age groups (two years old (yo), four yo, 10 yo with high semen rejection (10 HR), and 10 yo with low semen rejection (10 LR) were used in this study to evaluate the productivity and characteristics of fresh semen. The results showed that the pre-freezing and post-freezing semen rejection rate of 10 HR group was higher (P0.05) than the other groups. The four yo group had the percentage of second semen ejaculation each collection was higher (P0.05) than the other groups. Furthermore, semen volume, sperm concentration, and total sperm concentration significantly increased (P0.05) until four yo and then decreased (P0.05) in 10 yo groups. The 10 HR group had the volume and total sperm concentration significantly different (P0.05) with a group of 10 LR. Total sperm motility, individual motility, and mass movement were lower (P0.05) in 10 HR than the other groups. In conclusion, age differences of bulls can affect the productivity and characteristics of fresh semen.